Efeitos de nanopartículas de La2O3 em ratos e biodistribuição de elementos por LA-ICP-MS - Heidrich, Graciela Marini (2018)
The aim of this work is to evaluate possible effects caused by oral administration of La2O3-NP in rats. Due to the lack of toxicological knowledge of La2O3-NP, the acute oral toxicity test, according to OECD 425 guidelines, was initially performed. For this purpose, four doses of La2O3-NP (5 mg kg-1, 50 mg kg-1, 300 mg kg-1 and 2000 mg kg-1 per body weight), where no behavioral changes, symptoms of intoxication or mortality were observed. According to the histological analyzes of the liver, doses of 300 mg kg-1 showed small hepatic lesions, so, for the chronic toxicity study of, doses below 300 mg kg-1 were used. The second part of the study consisted in the evaluation of chronic toxicity of La2O3-NP for a period of 31 days. La2O3-NPs were also administered orally. For the test, animals were divided into 4 groups (control, 1 mg kg-1, 10 mg kg-1 and 100 mg kg-1 per body mass). Analysis of biodistribution of La, macrominerals and microminerals elements in different organs, through determination by ICP-MS and bioimaging by LA-ICP-MS. In addition, toxicological parameters were also analyzed through biochemical analyzes in blood serum to evaluate possible hepatic and renal lesions. However, no changes were observed in creatinine, urea, gamma glutamyltranspeptidase, alanine aminotransferase and aspartate transaminase levels, both in the control animals with the animals treated with the NPs. According to the results, the lethal dose (LD50) for administration of La2O3-NP is greater than 2000 mg kg-1. Oral administration of La2O3-NP at concentrations equal to or lower than 100 mg kg-1 over a period of 31 days did not cause significant changes in biochemical parameters and in the mass of rat organs, which did not demonstrate toxicological characteristics of this nanomaterial. Analysis of biodistribution of La2O3-NP, shows that La is most accumulated in liver, kidney and heart. Determination of macrominerals and microminerals, can be observed that the kidney and liver were the most affected organs in the variation of the elemental concentration.